Anaphylactoid reactions following red blood cell transfusion in a patient with previously undiagnosed immunoglobulin a deficiency: Case report - Güngör, Hande; Uludağ Yanaral, Tümay; Uzunoğlu, Emine; Karaaslan, Pelin (AVES, 2023)
A 73-year-old, 104 kg female patient was hospitalised for debulking and low anterior colon resection operations. Anaphylactoid symptoms devel-oped when administering erythrocyte suspension and fresh frozen plasma. Through the immediate haematology department consultation, it was found that the patient might possibly have immunoglobulin A deficiency. Immunoglobulin A level was found to be very low in the patient’s blood sample, which was sent intraoperatively to verify the diagnosis. This case report discusses a sudden anaphylactic reaction that occurred as a result of a blood transfusion in a previously undiagnosed immunoglobulin A deficiency.
Keywords: Anaphylaxis; Blood Products; Immunoglobulin A; Perioperative Care; Transfusion